Magnetic biocatalysts of pectinase : synthesis by macromolecular cross-linker for application in apple juice clarification - Nouri, Marjan (Array, 2021)
Research background. Pectinase enzyme has become a valuable compound in beverage industry. One of the most significant concepts to overcome the drawbacks of using industrial enzymes is their immobilization. In the present study, magnetic chitosan microparticles were utilized as a substrate for pectinase immobilization. New methods of enzyme immobilization involve the use of non-chemical cross-linkers between the enzyme and the substrate. The aim of this study is to immobilize the pectinase enzyme using polyaldehyde kefiran as a macromolecular cross-linker on magnetic particles. Experimental approach. Pectinase was immobilized in four steps: relative oxidation of kefiran and its application as a cross-linker, production of magnetic iron(II) iron(III) oxide (Fe3O4) microparticles, coating of magnetic Fe3O4 microparticles with chitosan, and immobilization of the enzyme on the substrate, prepared by the use of oxidized kefiran cross-linker. Parameters such as cross-linking concentration, time and ratio of chitosan magnetic microparticles to enzyme were optimized. Fourier-transform infrared spectroscopy (FTIR), dynamic light scattering, transmission electron microscopy, and vibrating sample magnetometer were used to identify the groups and investigate the structures. The biochemical properties (stability of enzyme activity at different pH, temperature and time), enzyme reusability, kinetic parameters (Km and νmax) and apple juice turbidity, using free and immobilized pectinase enzymes, were also measured. Results and conclusions. Cross-linker concentration, cross-linking time and the ratio of magnetic Fe3O4 microparticles with chitosan to enzyme were important factors in activity recovery of pectinase. FTIR analysis correctly identified functional groups in the structures. The results showed that after enzyme stabilization, the particle size and molecular mass, respectively, increased and decreased the magnetic saturation strength.